Stock market and economic growth in ASEAN-5 / Siti Muliana Samsi - Siti Muliana , Samsi (2017)
The aim of this study is to analyze the effect of the financial crisis on economic growth through stock market in ASEAN-5. In particular it analyzes to what extent the financial and non-financial markets effect economic growth through three indices, stock markets, banks and real estate. The study used quarterly data covering the period 1990:Q1 to 2016:Q4 for Indonesia, Malaysia, the Philippines, Singapore and Thailand. Using analysis of cointegration, vector error correction model (VECM), Granger causality test, impulse response function (IRF) and variance decomposition analysis (VDC), the study found that the effects of stock market on economic growth were different among the countries. The empirical finding from PECM shows that the significant effects of stock market and banks index on economic growth is higher as compare to real estate. This significance effect of stock market on economic growth in Indonesia, Singapore and Thailand is due to the short-run capital inflows from foreign investors. The financial sector in particular the stock market tends to stimulate and promote economic growth when monetary authorities adopt liberalized investment and openness policies, improve the size and the regulations of the stock market, and increase the macroeconomic stability. Interestingly, the effect of sectoral stock indices via stock market, banks and real estate on economic growth is different when the Asian and global financial crises were considered in the model. The findings show that the global financial crisis has no significant effect on economic growth in ASEAN-5 when various sectors are considered into the model. This finding provides evidence that stock market and banking indices contain leading information for economic activity.